Combination of Iron Chloride and Polyacrylamide as Coagulant-Flocculants to Remove Pollutants in Dye Wastewater - Ishak, Siti Aisyah (International Journal of Integrated Engineering, 2019)
Dye Industrial developments have been increasing over the years and have created various environmental problems for water resources. This study was carried out in order to reduce the concentration of colour as well as the COD concentration by coagulation (Iron chloride) and flocculation (Polyacrylamide) using a standard jar test apparatus. The coagulation and flocculation processes were completed using Response Surface Methodology – Central Composite Design in order to see the effect of pH on iron chloride and polyacrylamide at optimum conditions. The analysis of zeta potential was done at various pH levels to compare the reduction of COD and colourant at various levels. Further analysis using the sludge produced included measuring for phytotoxicity using Lactuca sativa seeds. The treatment showed the highest colour removal with 95% (31 pt. co) and 92.0 % (42 mg/ L) COD reduction at pH conditions of around 5.4, 375 mg/ L of coagulant and 28 mg/ L of flocculant. Charge neutralization occurred when the pH moved to acidic region of 4-6. It was found that pH significantly influenced Iron chloride and Polyacrylamide for both responses (colour and COD). The phytotoxicity assessment indicated the mortality rate is increased with an increase in sludge concentration. Results revealed that FeCl3PAM at 100% undiluted dye sludge recorded the highest mortality rate.